Preliminary analytical study of two Egyptian mummies from Anthropological Museum of Athens - Καραμάνου, Αναστασία (Πανεπιστήμιο Πελοποννήσου, 2017)
The current thesis presents the preliminary analytical study of two Egyptian mummies from Anthropological Μuseum of Athens. The mummies were investigated with visual examination, photograph documentation and sampling procedure in order to estimate their preservation state. All the samples were examined macroscopically and stereoscopically. Samples of bandages, tissue, hairs, balms, filling material of plant, two beads and possible gold residues were analyzed; Optic microscopy, SEM/EDEX, ATR/FTIR, and portable XRF analytical techniques were used; Microbiological analysis also was conducted with the use of Optic microscope and fungus cultivation. The results are discussed making the analytical methodology used, capable for the preliminary study of the mummies. As conclusion the mummies are in bad preservation state and immediate conservation plan is required. Future examination aims are included too.
Keywords: Μούμιες -- Αίγυπτος; Μούμιες -- Συλλογή και διατήρηση; Μούμιες -- Συντήρηση και αποκατάσταση; Ανθρώπινα λείψανα (Αρχαιολογία) -- Ανάλυση; Αιγυπτιακές μούμιες; Ανθρώπινα λείψανα; Συντήρηση αρχαιοτήτων